Strain elastography of tongue carcinoma using intraoral ultrasonography: A preliminary study to characterize normal tissues and lesions - Ogura, Ichiro (Imaging Sci Dent, 2018)
PURPOSE: The aim of this study was to evaluate the quantitative strain elastography of tongue carcinoma using intraoral ultrasonography. MATERIALS AND METHODS: Two patients with squamous cell carcinoma (SCC) who underwent quantitative strain elastography for the diagnosis of tongue lesions using intraoral ultrasonography were included in this prospective study. Strain elastography was performed using a linear 14 MHz transducer (Aplio 300; Canon Medical Systems, Otawara, Japan). Manual light compression and decompression of the tongue by the transducer was performed to achieve optimal and consistent color coding. The variation in tissue strain over time caused by the compression exerted using the probe was displayed as a strain graph. The integrated strain elastography software allowed the operator to place circular regions of interest (ROIs) of various diameters within the elastography window, and automatically displayed quantitative strain (%) for each ROI. Quantitative indices of the strain (%) were measured for normal tissues and lesions in the tongue. RESULTS: The average strain of normal tissue and tongue SCC in a 50-year-old man was 1.468% and 0.000%, respectively. The average strain of normal tissue and tongue SCC in a 59-year-old man was 1.007% and 0.000%, respectively. CONCLUSION: We investigated the quantitative strain elastography of tongue carcinoma using intraoral ultrasonography. Strain elastography using intraoral ultrasonography is a promising technique for characterizing and differentiating normal tissues and SCC in the tongue.